Performance based payment dan kepuasan kompensasi dalam pemberian jasa pelayanan kapitasi jaminan kesehatan nasional bagi tenaga kesehatan Puskesmas di Kabupaten Ende - Mariane Erika Pay; Andreasta Meliala; Dwi Handono (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Performance based payment and compensation satisfaction in the distribution of capitation medical services of national insurance health for primary health care workers in the District of EndePurpose: To evaluate the implementation of the distribution of capitation services using a performance-based payment system in Ende Regency. Methods: This research is qualitative using a case study design. Study subjects 23 people were selected by purposive sampling technique. The research location was in the Health Office and 2 puskesmas. Data collection uses interview guides and document reviews. Qualitative data is presented in the form of narratives, pictures and tables. Respondents' answers will be displayed in the form of quotes. Results: Providing compensation for services still causes dissatisfaction. Health workers are not satisfied with the reduction due to tardiness, are not involved in the calculation of services, doctors feel the tax deduction is too large, the number of health workers is in accordance with the services provided. Puskesmas assessment team has been working based on existing regulations. Conclusions: There is a need for supervision, supervision, monitoring and evaluation from the Ende District Health Office for the distribution of capitation services. Puskesmas leaders and staff must be able to work together and coordinate well in making puskesmas policies and implementing these policies.